Extraction and comparative study of green energy using different types of biowaste material. (2022) - Singh, Palvinder; Bhargava, Cherry; Kumar, Manish; Singh Maturia, Abhilash; Singh, Pramod K.; Kumar Sharma, Pardeep; Sachdeva, Amit
Abstract: Wind and solar green energy sources have increasingly been widely used by businesses and researchers worldwide. In the literature, these energy sources have also been represented. For these developments to be universal, these energy sources need more construction costs, more maintenance costs, and more operating space. An energy storage system is to be built to solve these issues, allowing us to store energy during lean hours and supply energy at a low cost later. These technologies, such as the battery, cell, and supercapacitor, can very easily store energy and energy distribution speeds. This energy sources have a high current for a limited period. We need electrode material and electrolyte material mentioned in previous research papers to make these energy sources. Due to its excellent electrical conductivity, excellent stability, and high specific surface area, electrode materials such as carbon and carbon-based materials are generally used. In these energy sources, these materials serve as dielectric materials. Carbon and carbon-based materials have recently been derived from bio-waste materials. These bio-waste products are bio-waste for agriculture, bio-waste for tree leaves and bio-waste from fruits. The use of these bio-waste products aids in the disposal of waste and turns waste into a vital resource. These products for bio-waste are readily available at no cost. The approaches used by researchers to obtain from bio-waste are explored in this study research paper on the availability of different bio-waste materials.